Algebra 2 (1st Edition)

Published by McDougal Littell
ISBN 10: 0618595414
ISBN 13: 978-0-61859-541-9

Chapter 4 Quadratic Functions and Factoring - 4.2 Graph Quadratic Function in Vertex or Intercept Form - Guided Practice for Examples 5 and 6 - Page 248: 15


$$ f(x) =-x^2 -4x$$

Work Step by Step

We are asked to put this equation in standard form. Thus, we first use the FOIL method. Next, we simplify until the equation is put in the form $y=ax^2 +bx+c$. Doing this, we obtain: $$f(x) =-(x+2)(x+2) +4 \\ f(x) = -(x^2+2x+2x+4) +4 \\ f(x) =-x^2 -4x -4 +4 \\ f(x) =-x^2 -4x$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.